Collage as a Reflective Tool: Teachers’ Perspectives on Forests and Urban Environments - Thorén Williams, Alexina; Sanders, Dawn; Svensson, Maria (Design and Technology Education: An International Journal, 2024)
The study aims at professional development directed towards finding new pathways in education for and in sustainable development. In this study, we consider how primary teachers from two schools in Gothenburg, Sweden, experience the forest and the urban area as potential learning environments.  This study focuses on teachers’ perceptions (understanding) and experiences (emotional) of two places, the urban area, and the forest. To make visible teachers' relationships with the urban area and the forest, we use collage inquiry as a research method to stimulate teachers’ reflection, conversation and writing about the forest and urban area. Primary teachers from three schools in Sweden participated in the study and made collages The collage inquiry brought out their emotions, perspectives, and curiosity about the forest and the urban area described in three themes; temporarily situated, place dependent and emotionally connected. Knowledge of teachers' perceptions and experiences ensures opportunities to deepen the ability to teach technology beyond the classroom.  To bridge between biology and technology and compare ecological and technological systems constitutes a possible basis for continued work and development of teaching for sustainable development.